Suboptimal peak inspiratory flow rate: a noticeable risk factor for inhaler concordance in patients with chronic airway diseases - Yan Chen; Weiwei Meng; Ruoyan Xiong; Zhiqi Zhao; Huihui Zeng (BMJ Open Respiratory Research, 2024)
Background Inhaler concordance and the peak inspiratory flow rate (PIFR) are important determinants of treatment effects in patients with chronic airway diseases. Adequate PIFR is required for driving aerosol medication into the lower respiratory tract. However, the relationship between them has not been discussed previously. This study aimed to describe the characteristics of inhaler concordance and PIFR in Chinese patients with chronic airway diseases and discuss the associated variables and the relationship between them.Methods In this single-centre, observational study, a total of 680 patients with chronic airway diseases were enrolled from July 2021 to April 2023. We collected data on the socio-demographic and clinical variables of inhaler concordance using the test of adherence to inhalers (TAI) and PIFR. Multivariate logistic regression was conducted to examine variables related to inhaler concordance and PIFR.Results A total of 49.4% of patients had low concordance. Patients with chronic obstructive pulmonary disease (COPD) were more concordant than patients with asthma (mean TAI score: 43.60 vs 41.20; p<0.01), while there was no difference in concordance between the asthma-COPD overlap group and the asthma or COPD group. Suboptimal PIFR (adjusted OR, 1.61; 95% CI 1.04 to 2.51) increased the risk of poor concordance among all patients, while triple therapy (adjusted OR, 0.60; 95% CI 0.35 to 0.86) reduced the risk. A total of 54.9% of patients had suboptimal PIFR. Older age, lower educational level, use of dry powder inhalers and lower forced expiratory volume in 1 s % predicted were significantly correlated with insufficient PIFR. Subgroup analysis revealed a greater proportion of patients with insufficient PIFR during exacerbation than during the stable phase (61.7% vs 43.5%, p<0.001).Conclusion Inhaler concordance was low, and suboptimal PIFR was a risk factor for poor concordance among Chinese patients with chronic airway diseases. In addition, current inhalation devices may not be suitable, and PIFR reassessment should be considered for patients with COPD during exacerbation.Trial registration number The study was registered in chictr.org.cn (ChiCTR2100052527) on 31 October 2021.